Policy Analysis of Mango's Agribusiness Development (A Case in Cikedung District, Indramayu Regency) - Rasmikayati, Elly; Elfadina, Ellisa Agri; Kusumo, Rani Andriani Budi; Saefudin, Bobby Rachmat; Supriyadi, Supriyadi (Jurnal Manajemen dan Agribisnis, 2020)
Mango is a popular commodity with local demand and exports are quite high each year. However, there is a fluctuation of land tenure area and the number of mango trees in Cikedung district, Indramayu regency that can affect the quantity of mango produced by farmers. This study aims to analyze the policies that have been carried out by the Ministry of Agriculture of the Republic of Indonesia related to the development of mango agribusiness and compile policy recommendations for developing mango agribusiness in Cikedung District, Indramayu Regency. The method used in this research is a survey method to 130 respondents. Data analyzed using the descriptive statistics analysis and Tinbergen model. The results showed that the type of government policies that has been accepted by some mango farmers in Cikedung district is very limited, the only grant of mango seed. The development of mango agribusiness policy that can be used to increase the land tenure area so that it impacts on increasing quantity of mango harvest, namely grant of agricultural production, land lease, seed grant, price subsidy of agricultural production facilities, and capital loans.Keywords: policy analysis, agribusiness development, mango farming, land area, Tinbergen model